Bodily Information and Top-Down Affective Priming Jointly Affect the Processing of Fearful Faces - Yu, Alessandra Nicoletta Cruz; Iodice, Pierpaolo; Pezzulo, Giovanni; Barca, Laura (Frontiers in Psychology, 2021)
According to embodied theories, the processing of emotions such as happiness or fear is grounded in emotion-specific perceptual, bodily, and physiological processes. Under these views, perceiving an emotional stimulus (e.g., a fearful face) re-enacts interoceptive and bodily states congruent with that emotion (e.g., increases heart rate); and interoceptive and bodily changes (e.g., increases of heart rate) influence the processing of congruent emotional content. A previous study provides evidence for this embodied congruence, reporting that experimentally increasing heart rate with physical exercise facilitates the processing of facial expressions congruent with that interoception (fear), but not those conveying incongruent states (disgust or neutrality). Here, we investigate whether the above (bottom-up) interoceptive manipulation state interacts with the (top-down) priming of affective content, which is known to influence emotional processing as well. After rest or exercise, participants performed a gender-categorization task of happy, fearful, and neutral faces, which were preceded by positive, negative, and neutral primes. We hypothesized that if emotional processing is the result of an interoceptive inference that integrates (top-down) affective primes and (bottom-up) interoceptive streams, then positive and negative primes should facilitate the processing of happy and fearful faces, respectively, when participants have emotion-congruent bodily states (i.e., high heart rate). We found that negative priming facilitates the processing of fearful faces, over and above high heart rate. However, positive priming does not facilitate the processing of happy faces. While this asymmetry requires further investigation, our findings promisingly indicate that the processing of fearful faces integrates bottom-up interoceptive streams and top-down primes.